Malibongwe conferentie: optreden Gerda Havertong en band tijdens de slotavond in Paradiso, Amsterdam - Veldt, Matthijs
Malibongwe conferentie: optreden Gerda Havertong en band tijdens de slotavond in Paradiso, Amsterdam.